PRINCIPLES OF NURSING DIAGNOSIS AND TREATMENT IN BLEEDING AND BLOOD LOSS SYNDROME - N.A. Kochkarova,; D.M. Gapparova, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article aims to make nurses working in preventive treatment institutions and family polyclinics mature in all respects, to acquire sufficient knowledge, skills, and abilities in specialized disciplines, to further improve medical assistance in self-management and counseling, and to acquire new theoretical knowledge through practical skills. aimed at acquiring strengthening, psychological care skills